Domiciliary care and migrant domestic workers: grasping the new institutional landscape. Issue 9 (19th August 2014) - Abrantes, Manuel; Williams, Colin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This article addresses the nexus of domiciliary care demand and vulnerable migrant women recruited as domestic workers, focusing on the role of two types of organizations operating at the meso-level: commercial companies and nongovernmental organizations. The purpose is to identify the ways in which these organizations seek to change the dynamics of paid domestic work and explore how they attempt to shape the voice of domestic workers and their employers. Design/methodology/approach An actor-based approach is applied to the metropolitan area of Lisbon, a relevant setting for empirical research given local developments in the realms of care, employment, migration, and public policy. Qualitative case study techniques of data collection and analysis are adopted. The analysis is based on institutional records and open-ended interviews with managers of commercial companies and activists of nongovernmental organizations. Background contributions are drawn from interviews with domestic workers, private employers, and privileged informants. Findings Data from fieldwork demonstrate that the organizations under examination offer a significant and innovative contribution to raise and shape the voice of both paid domestic workers and their employers. More than introducing a radical perspective on the nature or content of domestic work, these organizations are engaged in stimulating a more efficient and sustainable organization of paid care in private households. Research limitations/implications Given the novelty of the approach, the present analytical endeavour is chiefly exploratory and much of the regulatory interactions and behavioural patterns remains in the penumbra. Suggestions for future research include a more systematic and detailed scrutiny of the role of organizations, as well as the incoporation of other institutional actors such as state bodies and charitable organizations active in this field. Originality/value The original emphasis on a meso-level of analysis and the choice of empirical qualitative examination – against a normative landscape of public regulation at the top and individualized actors down below – furthers our understanding of the topic and paves the way to promising developments in both scholarly research and policy debate.